FRI0459 Characteristics and Long-Term Outcome of 122 Patients with Takayasu Arteritis. (10th June 2014) - Comarmond, C.; Mirault, T.; Cluzel, P.; Koskas, F.; Chiche, L.; Gaudric, J.; Messas, E.; Cacoub, P.; Saadoun, D.
Abstract : Background: Takayasu arteritis (TA) is a chronic inflammatory disease that primarily affects large vessels, such as the aorta and its main branches. Objectives: To report clinical features, morphologic findings, treatment and long-term outcome of a large cohort of patients with TA. Methods: We performed a retrospective multicenter study of characteristics and outcome of 122 patients with TA fulfilling the American College of Rheumatology criteria. Results: The median age [Q1; Q3] at onset of symptoms was 35.4 [24.4; 46.3] years and with a predominance of females (n=103, 84.4%). The median delay of diagnosis was 10 [0; 46.25] months. The most common clinical findings were vascular bruits (n=66, 54.1%), upper extremity blood pressure discrepancy >10 mm Hg (n=57, 46.7%), and unequal or absent pulses (n=55, 45.1%). Major complications at diagnosis were hypertension (n=41, 33.6%), aortic regurgitation (n=24, 19.7%), aneuvrysm (n=30, 24.6%) and retinopathy (n=3, 2.1%). Fifty five (45%) patients had extensive disease at diagnosis according to Numano type V. Twenty four (19.7%) patients had another inflammatory or auto-immune disease associated to TA. Stenotic lesions were 3.1-fold more common than were aneuvrysms (77.9% versus 24.6%, respectively). Revascularization procedure was required for 53 (43.4%) patients. The median delay between diagnosis and first surgery or endovascular intervention was 5 [0; 17.5] months. Medical therapy (i.e. corticosteroids) was prescribed in 107 (87.7%) patients. The median delay in initiation of corticosteroids was 1 [0; 5] months. Eighty one (66.4%) patients required additional immunosuppressive agent. The median delay in initiation of the first immunosuppressor was 11 [2; 29.5] months. Fifty four (44.3%) patients relapsed after a median follow-up of 64.5 [24.9; 124.5] months. The median relapse-free survival was 16 [7; 62.25] months. Conclusions: Most patients with TA require prolonged and intensive medical therapy. However, relapse and revascularization are frequents, occurring in nearly half of patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5926